Implementation of ISO 9000 in Industrial Libraries:A Case Study - Date, Dhanashree A.; Gokhale, Pratibha A. (Journal of Information and Knowledge, 1999)
Fierce competition in the international market has heightened the need for qualitative delivery of products and services. The internationally accepted ISO standards and their certification help to guide and audit an organization’s quality management practices. This paper is a case study on interpreting ISO 9000-4: 1992 (Quality Management and Quality Systems elements-Guidelines for services) and applying it to library procedures, so as to evolve a process based quality improvement within a library. It gives an analysis of a survey done for some industrial libraries in Mumbai. The data analysis reflects the level of quality in the services of these libraries and benchmarks their low quality indicators. Observations and conclusions are drawn and avenues for further research in this area are identified.